Aspectos de crescimento, fisiológicos e bioquímicos de capuchinha submetido à doses de prolina como atenuante da salinidade - Targino, Vitor Araujo (2024)
Salinity is one of the major obstacles in agriculture in semi-arid regions, as it affects the physiological processes, growth, and production of various crops. Therefore, the use of salinity stress alleviators is extremely important, as it allows for the use of saline water for agricultural purposes. Among these, proline stands out as an alternative to mitigate the damage caused by this stress. Thus, the objective of this study was to evaluate the effect of proline application as a mitigating agent for the detrimental effects of salt stress on the growth, gas exchange, and metabolism of nasturtium. The experimental design used was completely randomized in a 5 (electrical conductivities - ECe: 0.0; 1.50; 3.00; 4.5; 6.5 dS m-1) x 4 (proline concentrations - Pro: 0.0; 5.00; 10.0; 15.00 mM) factorial scheme, with six replications. In article I, growth, gas exchange, chlorophyll index, and chlorophyll a fluorescence were evaluated. In article II, the accumulation of fresh and dry mass of leaves, stem and root, number and weight of flowers, phenolic compounds, vitamin C, reducing and soluble sugars were evaluated. The application of proline was beneficial to nasturtium plants, increasing the number of leaves, stem diameter, root length, biomass accumulation, weight and number of flowers, total phenolic compounds, levels of reducing and soluble sugars. It also promoted an increase in the activity of vitamin C in plants subjected to severe salt stress at 4.75 dS m-1. The concentration of 15.0 mM proline associated with moderate salinity from irrigation water at 3.0 dS m-1 stimulates gas exchange, resulting in higher net photosynthesis, transpiration and stomatal conductance of T. majus.